(untitled) (Medical Forum Monthly, 2024)
Objective: objective of the study was to explore the Stigma, attitude and practices with special reference to TB in Urban areas. Study Design: Descriptive study Place and Duration of Study: This study was conducted in UC-49. Tehsil Malikwal District Mandi Bahawaldin from Jan-2013 to March-2013. Materials and Methods: To gather the data on set objective a structured questionnaire was implemented. To collect the data a sample of 70 was interviewed after verbal consent. Tool was refined as per the highlighted suggestions of pre-testing under similar environment. Data was entered in EpiData software and analyzed in SPSS. Results: Tables show the participation of both male and female as 70:30% respectively. In case of TB symptoms; Doctor or other medical worker was consulted for sharing by 91.4% respondents, 71.4% respondents would like to visit health facility (Government or Private), 14.3% visit the pharmacy for treatment, 30% were those who visit the health facility when they observed TB signs especially duration of cough, 65.7% urban residents visit the care center as soon they realize they had TB, 8.6% hate TB patients, 30% response friendly but avoid TB patients, 40% show sympathy toward TB patients, and 60% were said that the life of Tb patients were poor. Conclusion: In spite of health interventions aimed at awareness, treatment and rehabilitation of TB in Pakistan, the country still stands distinctively among the nations where TB is sky rising. The government and civil society need to move ahead from policy level to practical implementation of measures to prevent TB. At cultural perception level, there is a need to remove misconceptions about TB being the one that severely bars the social life mingling.